Spiritualitas dan Kewirausahaan: Eksplorasi Peran Praktik Tasawuf Dalam Kesuksesan Usaha - Rahmat Lutfi Guefara (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This article examines the impact of Sufi practices on entrepreneurial success, with a specific focus on jeans entrepreneurs in Wonosobo Regency. This research employs a qualitative approach within the framework of ethical Sufism to understand how spiritual values influence business behavior. The study subjects include three entrepreneurs, with data collected through observation, in-depth interviews, and documentation. Descriptive analysis indicates that the continuity of worship practices, especially prayer, significantly contributes to the formation of resilient and integrity-driven entrepreneur characters. The findings confirm that entrepreneurs who are consistent in their worship practices tend to experience better business stability and growth. This study confirms that integrating Sufism into entrepreneurship not only enriches the personal dimension of entrepreneurs but also generates competitive advantages. These conclusions suggest the importance of considering spiritual factors in modern business development strategies.